Budaya Tradisional Tarian Lahbako Jember Sebagai Upaya Pelestarian Sekaligus Pengenalan Kepada Generasi Muda - Destri Aulia Wulandari; Nazala Zaikumar Elfa Rizqi; Netti Mahdalena Siregar (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
This research will discuss the community's efforts in maintaining the heritage of the ancestors given, namely the Lahbako dance. Lahbako dance is a typical Jember dance, where this dance exists to show a series of tobacco processing from planting to packaging tobacco. This arian can be said to be a tradition that is carried out every time tobacco planting and has become one of the icons of the city of Jember. It is well known that technological development has been increasingly rapid, and young people are starting to be reluctant to learn or just find out what has become the history of their own nation. The existence of the Lahbako dance which used to be a tradition during the harvest season, is now also used as a tourist attraction, so it can be said that there is a shift in cultural functions. Therefore, efforts are needed to introduce all groups, especially young people so that they can continue to preserve or innovate the culture. In this study we use Robert K. Merton's theory of Structural Functionalism, which emphasizes the need to understand the many functions associated with society, in order to maintain the social structure in society. The functions in question are dysfunction, latent function, and manifest function. In this research using qualitative research methods, with an ethnographic approach.